(untitled) (Revista Educação, Artes e Inclusão, 2024)
The theme of interest in this experience report is on teaching materials aimed at teaching visually impaired students that occurred in a teaching experience conducted in a math degree with students of support service in Southern Bahia/Brazil, among the specificities of Inclusive Education. The research question seeks to identify the need for inclusive teaching materials in Special Education. As a general objective, we try to understand the aspects observed by EE teachers about the materials that meet the needs of students. Methodologically, to confirm the findings arising from the experience, we collect data via questionnaires sent to schools, institutes, and Inclusive Education center teachers. To this end, we present the following question: Have you realized improvements in students’ learning using inclusive teaching materials to overcome their difficulties? We analyzed quantitative data using Discursive Textual Analysis. Then, a category named Specialization in Inclusive Education emerged and led to our final considerations, which suggest a need for professional development of teachers working in inclusive classrooms starting from their university degrees, regardless of their knowledge area.